Simulation-Based Virtual Validation of Functional Limiting Positions - Ehlert, Matthias; Stockinger, Andreas (Research in Tolerancing, 2024)
In addition to a classical toleration of components and assemblies, Computer-Aided Tolerancing became an indispensable engineering discipline in recent years—especially in the context of a series manufacturing of a product. Taking 3D geometries, resulting lever ratios, assembly sequences and various reference systems as well as statistical approaches into account, it already enables complex tolerance calculations of products that are subject to variations arising from the manufacturing process. One of the main premises for these kinds of simulations refers to the presumed rigid behavior of all contributors. As a direct consequence of that assumption this chapter describes a virtual approach, based on specified Key Product Characteristics that takes both elasticities and a possible non-linear system behavior in the simulation into consideration. This proceeding to include materialities and interactions between tolerance affected components increases the forecast quality of the tolerance simulation in terms of a more realistic prediction. The demonstrator used is the entry area of an automobile, where the tightness of the system against water, dust, or other media needs to be ensure